Identification of factors that influence student satisfaction from the analysis of voice messaging from WhatsApp: a case study - Chamorro-Atalaya, Omar; Aquije-Cardenas, Giorgio; Carranza-Noriega, Raymundo; Moreno-Chinchay, Lilly; Medina-Bedón, Yurfa; Alejos-Ipanaque, Rufino; Tasayco-Jala, Abel; Gonzales-Saldaña, Susan (International Journal of Evaluation and Research in Education (IJERE), 2025)
In these times when there is talk of a return to a new normality in education after what happened due to the pandemic, it is necessary to permanently evaluate the perception of student satisfaction, contributing to the results obtained through traditional methods such as the survey, with methods in which open opinions can be analyzed as in the case of voice analysis. In this sense, this article describes a case study, which aims to identify the factors that influence student satisfaction with respect to teaching performance, based on the analysis of WhatsApp voice messaging. The study has a qualitative approach, exploratory level and non-experimental design. It was possible to identify various factors grouped into five categories: i) planning; ii) didactic strategies; iii) communication; iv) administration of the class session; and v) professional and personal characteristics of the teacher. Therefore, it is concluded that it is possible to close the gaps between the factors that are sensitive and relevant for the university, when a questionnaire with delimited questions is applied to observe only some factors of student satisfaction, with respect to those sensitive factors and relevant to students, by analyzing their comments from the use of voice messaging from mobile applications.